PERANCANGAN PROGRAM PENGGAJIAN PADA PT. KORMA JAYA UTAMA JAKARTA - Setyawati, Nuraini; Fadholi, Arief (EDUTECH CONSULTANT, 2018)
Right now in this era of globalization, the information technology is speeding up. The computer is a device that was created to facilitate human work, while achieving good progress in the manufacture of hardware and software. PT. Korma Jaya Utama requires a computerized system that supports and provides good service for its employees. That's why the author tries to make the Final Project on Payroll Program Design at PT. Korma Jaya Utama Jakarta. PT. Korma Jaya Utama is a company engaged in the food processing industry, especially soy sauce. The existing system at PT. Korma Jaya Utama is done semi-computerized, so it has frequent constraints such as errors in the calculation and payment of salary, search data long enough, recording absent absences are still done manually, errors in calculating overtime until making reports that require time long. So with a computerized system is the best solution to solve the problems existing in this company, as well as with a computerized system can be achieved an effective and efisisen activities in supporting activities in this company.